2008
DOI: 10.4314/sajrs.v30i2.25990
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of players\' performances in the first cricket Twenty20 World Cup series

Abstract: The purpose of this paper is to show how batting and bowling performance measures for one-day internationals can be adapted for use in Twenty20 matches, specifically in the case of a very small number of matches played. These measures are then used to give rankings of the batsmen and bowlers who performed best in the first Twenty20 World Cup Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…The formula of the global strike rate GMSR is similar to MSR, but R then denotes the total number of runs scored and B the total number of balls faced by all batsmen in the match. The strike rate adjustment is RP0(MSR/GMSR) 0.50 which is similar to that of BP 26 in Lemmer (2008a), where BP 26 0e 26 x RP with RP0(SR/124.03) 0.50 in the latter case. After each match the batsman's score R is replaced by his adjusted score T0R x (MSR/ GMSR) 0.50 .…”
Section: Performance Measuresmentioning
confidence: 90%
See 1 more Smart Citation
“…The formula of the global strike rate GMSR is similar to MSR, but R then denotes the total number of runs scored and B the total number of balls faced by all batsmen in the match. The strike rate adjustment is RP0(MSR/GMSR) 0.50 which is similar to that of BP 26 in Lemmer (2008a), where BP 26 0e 26 x RP with RP0(SR/124.03) 0.50 in the latter case. After each match the batsman's score R is replaced by his adjusted score T0R x (MSR/ GMSR) 0.50 .…”
Section: Performance Measuresmentioning
confidence: 90%
“…Lemmer (2008b) showed that the traditional average, AVE, is not reliable as an estimator of the average in the case of a high proportion of not out scores, especially if a small number of innings have been played. In Lemmer (2008a) formula e 26 has been shown to be a much better estimator than AVE. The formula is e 26 ¼ ðsumout þ ð2:1 À 0:005 Â avnoÞ)sumnoÞ=n (1) with n the number of innings played, 'sumout' the sum of the out scores, 'sumno' the sum of the not out scores and 'avno' the average of the not out scores of the batsman.…”
Section: Performance Measuresmentioning
confidence: 97%
“…Here R represents the number of runs conceded by the bowler, O denotes the number of overs bowled, B represents the number of balls bowled, and W* is the sum of the weights of the wickets taken by the bowler. These weights were assigned for each wicket as explained by Lemmer (10).…”
Section: Methodsmentioning
confidence: 99%
“…Omdat spelers tot dusver nog baie min sulke wedstryde op internasionale vlak gespeel het, is dit nog nie mootlik om die prestasiemaatstawwe volledig te ontwikkel nie. In Lemmer (2008b) is aanbeveel dat die EDI-maatstawwe gebruik word. Vir kolfprestasie sal daar 'n geringe wysiging wees omdat die gemiddelde trefkoers volgens Varghese (2007) …”
Section: Twintig20 Krieketunclassified